A Critical Study of Wael B Hallaq’s Understanding of Islamic Law (Al-Qamar, 2021)
Today, Islamic law and the Islamic state are two topics that are hotly debated around the world. Among the Western scholars where Islam, the Prophet of Islam, the mission and teachings of the Prophet were the subject of interest, there are writings and speeches on contemporary Islamic state and Islamic law, Research and criticism have become important topics for many reasons. The most important of which is that the existence of the state in the West is in jeopardy and the main reason for this is the structure of the state that man has devised and which has established its supremacy over state institutions and state law. New forms of conflict began to emerge. Just as it is the way of the people of the West to turn to Islamic teachings in every matter. Similarly, in this case too, Islamic teachings were turned to research, and criticism on Islamic law and the Islamic State began. Although Ignác  Goldziher , Duacan Black Macdonald, Joseph Schacht, Norman Calder and Coulson had a lot to say about Islamic law. However, in the modern state context, no one worked on Islamic law. The responsibility for which was taken up by the eminent professor of the 21st century, Wael Hallaq. Hallaq's views on Islamic law are of twofold:• Hallaq does not consider Islamic law to be divine, but human evolutionary and variable.• According to Hallaq, in the past, Islamic law interacted with societies، but the rule of law remained stable while it was used later, especially due to the colonial effects that deprived it of its intended purpose.From the first point of view, he gives an overview of the conditions of the pre-proclamation of prophethood and the post-prophethood of Makki life. It also provides details of Madani life and the early evolutionary period, i.e the formative period, in the context of human theory of evolution.From 2nd point of view, Islamic law as a philosophy of morality is considered unworkable due to disagreement with modern nation-states.A research and critical review of the first point is under discussion in this article.
Keywords: Islamic law; Islamic State; Pre-Islamic Period; Islamic Period; Sources of Law; Formative Period